Analisis Hubungan Sanitasi Dasar Rumah dengan Resiko Kejadian Diare pada Balita - Asriani Asriani; Lili Eky Nursia N; Kiswanto Kiswanto; T. Alamsyah T. Alamsyah; Ernawati Ernawati (Jurnal Syntax Admiration, 2024)
Public health is affected by environmental health. Poor sanitation conditions will have a bad impact on human life, ranging from a decrease in the quality of the community's environment to the pollution of drinking water sources, which can lead to an increase in cases of diarrhea and other diseases. Clean water sources, healthy latrines, and standardized Wastewater Treatment Systems (SPAL) are essential. The purpose of this study is to analyze the relationship between basic sanitation conditions in households and the risk of diarrhea in toddlers. A quantitative method with a cross-sectional design was used in this study to identify the relationship between basic home sanitation, which includes the availability of clean water, the availability of healthy latrines, and the management of SPAL RT, and the possibility of diarrhea in toddlers. In this study, 63 samples of mothers from 74 populations had babies. To get information, questionnaires are distributed. The data were tested with chis-quare, and an error rate of 0.05% was taken into account. The results showed that the availability of clean water had a correlation with the possibility of diarrhea with a P_value of 0.004, the management of household waste sewers had a correlation with P_value 0.008, and the availability of good latrines had no correlation with the possibility of diarrhea with a P_value of 0.262. The results show that the Ujong Fatihah Health Center must continue to make efforts and socialization to increase public knowledge. Health staff must be educated by village officials on the importance of maintaining daily hygiene.